Investigation of organizational resilience through team operations in challenging conditions - Senturk, Melike (The University of Edinburgh, 2018)
In this study, I investigated the precursors and the outcomes of team resilience. In contrast to many resilience studies, which focus on low-probability, high-impact challenges, I investigated resilience in the face of high-frequency, low-impact challenges that teams can face in their operational environments. I conducted an extensive literature analysis of the field of resilience and on the basis of this constructed a model of team resilience by integrating insights from high reliability organizing, positive organizational scholarship, sensemaking and disaster resilience studies. I then tested and improved this model through an exploratory study of team behaviour in two “Escape Game” settings in which teams of 5 people worked through a series of puzzles under time-constrained and somewhat stressful conditions. Following the exploratory study, I developed the resilience model into an operationalizable format and tested it using seven runs of a simulation study involving 547 individuals in 68 teams. In the simulation, teams had to work both quickly and accurately whilst adapting to the changing conditions of a turbulent, competitive environment. Quantitative and qualitative data were collected on various team attributes, team resilience and team performance. I have used quantitative data as the main source of analysis and qualitative data as a supporting tool. Self-completion questionnaires, objective performance indicators, direct observation and post-simulation team and individual reflections were among the data collection tools that were used to obtain data. Team resilience shows highly significant associations with a range of objective measures of team performance. In turn, resilience is supported by several team attributes, including collective mental models, effective channels of communication and systems of information gathering and team cohesion. When teams faced challenges outside of their existing action repertoires their ability to improvise also contributed to resilience. Finally, when teams overcame (novel) challenges, this fed back into their accumulated knowledge through collective learning, enriching action repertoires. Together, these features bestow teams with resilience, which, in turn, enables them to overcome disturbances that might otherwise impede operational performance. In its final form, my resilience model serves as an explanation of the mechanisms of resilience and identifies its antecedents and outcomes. It can inform teams operating in uncertain, ambiguous and volatile work conditions about the capacities and capabilities they need in order to create and sustain resilience in daily operations.
Keywords: organizational resilience; team resilience; team operations; team performance; collective mental models; collective mindfulness